2016
DOI: 10.1017/cjn.2016.263
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Concussion-U Educational Program on Knowledge of and Attitudes about Concussion

Abstract: A Concussion-U educational program led to an immediate improvement in concussion knowledge and attitudes among elite male Bantam and Midget AAA hockey players. Increased knowledge was maintained at long-term follow-up, but improved attitude was not. Future studies should investigate whether similar educational programs influence symptom reporting and concussion incidence. In addition, they should focus on how to maintain improved concussion attitudes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…For example, collecting and sharing detailed descriptions of personal concussion experiences may help to move concussion knowledge to behavioral change that can reduce concussions injuries (Miyashita, Timpson, Frye, & Gloeckner, ). Other recommendations to sustain concussion knowledge include education messages customized to specifically target the age of the youth and the position played in the game of hockey (Eagles et al., ), multiple teaching modalities to encourage engagement (Echlin et al., ), and a celebrity or retired hockey player who had a concussion to speak at a workshop (Eagles et al., ). Future longitudinal studies could help determine the relationship between concussion education and the incidence of concussion over time.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, collecting and sharing detailed descriptions of personal concussion experiences may help to move concussion knowledge to behavioral change that can reduce concussions injuries (Miyashita, Timpson, Frye, & Gloeckner, ). Other recommendations to sustain concussion knowledge include education messages customized to specifically target the age of the youth and the position played in the game of hockey (Eagles et al., ), multiple teaching modalities to encourage engagement (Echlin et al., ), and a celebrity or retired hockey player who had a concussion to speak at a workshop (Eagles et al., ). Future longitudinal studies could help determine the relationship between concussion education and the incidence of concussion over time.…”
Section: Discussionmentioning
confidence: 99%
“…Kurowski, Pomerantz, Schaiper, Ho, and Gittelman (2015) found females were more knowledgeable about concussion as compared to males. Eagles et al (2016) also noted that studies with a significant increase in concussion knowledge may overestimate the effectiveness of their educational presentation when the study population is exclusively male. Other studies with non-Indigenous participants have also reported no statistically significant difference in knowledge levels following concussion education (Caron et al, 2015;Kroshus, Daneshvar, Baugh, Nowinski, & Cantu, 2014;Kurowski et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations